2022
DOI: 10.1101/2022.07.01.498408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human placenta exhibits a unique transcriptomic void

Abstract: We have recently demonstrated that the human placenta exhibits a unique genomic architecture with an unexpectedly high mutation burden(Coorens et al. 2021) and it is also well recognized that the placenta uniquely expresses many genes(Gong et al. 2021). However, the placenta is relatively understudied in systematic comparisons of gene expression in different organs. The aim of the present study was to identify transcripts which were uniquely absent or depleted, comparing the placenta with 46 other human organs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
2
1
0
Order By: Relevance
“…This is compatible with the decreasing effects that we observe for many genes (Jiang et al, 2021). On the other hand, we do show that our loci are actively expressed in early-to-mid-gestation placenta, which supports a more persistent role throughout pregnancy, and is also notable as many transcripts are missing in the placenta (Gong et al, 2022). In any case, we expect that follow-up studies can use our results to prioritise the most relevant genes and periods for each gene.…”
Section: Discussionsupporting
confidence: 89%
“…This is compatible with the decreasing effects that we observe for many genes (Jiang et al, 2021). On the other hand, we do show that our loci are actively expressed in early-to-mid-gestation placenta, which supports a more persistent role throughout pregnancy, and is also notable as many transcripts are missing in the placenta (Gong et al, 2022). In any case, we expect that follow-up studies can use our results to prioritise the most relevant genes and periods for each gene.…”
Section: Discussionsupporting
confidence: 89%
“…This is compatible with the decreasing effects that we observe for many genes ( 19 ). On the other hand, we do show that our loci are actively expressed in early-to-mid-gestation placenta, which supports a more persistent role throughout pregnancy and is also notable as many transcripts are missing in the placenta ( 20 ). In any case, we expect that follow-up studies can use our results to prioritize the most relevant genes and periods for each gene.…”
Section: Discussionsupporting
confidence: 72%
“…It has been observed that the placenta has a lower level of DNA methylation when compared to other somatic tissues (Ehrlich et al 1982;Robinson and Price 2015), with hypomethylation concentrated in partially methylated domains (Schroeder et al 2013(Schroeder et al , 2015. The placental transcriptome includes a greater number of genes that are uniquely expressed (Gong et al 2021) and uniquely depleted (Gong et al 2022) than other tissues, perhaps in part owing to the distinctive epigenomic landscape. This landscape includes many imprinted genes, which are expressed predominantly from either the maternal or paternal allele and are a feature of organisms that transfer nutrients directly to their developing offspring (Moore and Haig 1991).…”
Section: Introductionmentioning
confidence: 99%